Fast optimisation of tidal stream turbine positions for power generation in small arrays with low blockage based on superposition of self-similar far-wake velocity deficit profiles. (July 2016) - Stansby, Peter; Stallard, Tim
Abstract: Far wake velocities of a single horizontal axis three-bladed turbine in shallow flow have been measured previously in the laboratory and shown to have self-similar velocity deficit profiles. Wake velocities of arrays of turbines with one, two and three transverse rows have also been measured and simply superimposing the velocity deficits for a single turbine is shown to give accurate prediction of combined wake width and velocity deficit, accounting for variable downstream blockage through volume flux conservation. Array efficiency is defined as the ratio of total power generated to what would be generated by the same turbines in isolation. From prescribed initial turbine positions, generally determined intuitively or by practical considerations, adjusting the turbine positions to increase the power from each turbine, using the chain rule, shows that relatively small movements of 3–4 rotor diameters may increase array efficiency to over 90%. Highlights: Wake velocities of turbine arrays determined by self-similar velocity deficit superposition gives good predictions. Blockage correction is determined by volume flux conservation accounting for variable downstream blockage. Turbine positions are moved to increase individual, and hence total, power generation using the chain rule. Optimisation is undertaken for uni-directional and bi-directional flow. Turbine array efficiency is shown to increase to over 90% with relatively small turbine movements of 3–4 diameters.